(untitled) (International relations and international law Journal, 2020)
The article examines issues related to the formation of national security law under the influence of international law and the world legal order. The principles of international law are fundamental to the practical solution of issues of ensuring national security. National security law is influenced by the international legal system in general and international security law in particular. National security law is dependent on the state of the international legal system and the world legal order. The national security of the state directly depends on the state of international security at the global and regional levels. Without solving the problems of ensuring international security in a particular region of the world, in the interstate relations of two or more states, in the social world, there is no reason to assert the possibility of ensuring national security. The world legal order determines the state of public relations, strategic communications to ensure national security. In this regard, it becomes important to determine the lines of interaction of national security law with the world legal order system. The relevance of the research topic is determined by the general theoretical understanding of the features of the influence of the international legal system on the state of national security law and the formation of an effective impact on the solution of tasks to ensure national security. Key words: national security law, world legal order, international security law, principles of international law.